Generation Z’s Value Perception and Advocacy of Accommodation Promotions Offered by Online Travel Agencies - Sony, Alisa; Suwannarat, Pornlapas (Journal of Business, Innovation and Sustainability (JBIS), 2024)
The current study aims to assess the effectiveness of six accommodation promotions offered by online travel agencies (OTAs) for Generation Z customers (born from 1997 to 2012) and to examine the relationship between Generation Z’s perceived value of these promotions and their likelihood to advocate them. The study employed experimental research, using survey questionnaires, to gather data from 420 Generation Z respondents in Thailand. The findings reveal that the six promotions are equally effective, without any distinctive perceived value ratings or noticeable likelihood of recommending the promotion. Moreover, both price and emotional values have positive influences on Generation Z’s tendency to advocate the promotions. Therefore, OTAs are recommended to craft promotions that better resonate with Generation Z customers and leverage their potential to serve as promotion advocates by focusing on providing them with both price and emotional values.